Nationwide study of eculizumab in paroxysmal nocturnal hemoglobinuria: Evaluation of treatment indications and outcomes. (15th March 2023) - Schaap, Charlotte C. M.; Heubel‐Moenen, Floor C. J. I.; Nur, Erfan; Bartels, Marije; van der Heijden, Olivier W. H.; de Jonge, Emiel; Preijers, Frank W. M. B.; Blijlevens, Nicole M. A.; Langemeijer, Saskia M. C.; ,
Abstract: Eculizumab is an effective treatment for paroxysmal nocturnal hemoglobinuria (PNH). However, considering the risk of life‐threatening meningococcal disease, life‐long duration and costs, there are strict criteria for initiation of therapy. To evaluate the application and real‐world effectiveness of eculizumab in the Netherlands, a multicenter retrospective cohort study was conducted: indications and treatment outcomes were collected for 105 Dutch PNH patients. In all patients, eculizumab was initiated conforming to indications as formulated in the Dutch PNH guideline. According to recently published response criteria, 23.4% of the patients had reached a complete hematological response, 53.2% a good or partial response, and 23.4% a minor response after 12 months of therapy. In the majority of patients the response remained stable during long‐term follow‐up. The degree and relevance of extravascular hemolysis significantly differed between response groups ( p  = 0.002). Improvements of EORTC‐QLQc30 and FACIT‐fatigue scores were observed, however patients reported lower scores than the general population. A detailed evaluation of 18 pregnancies during eculizumab showed no maternal or fetal deaths, and no thromboembolic events during pregnancy. This study demonstrates that the majority of patients benefit from eculizumab when adhering to the indications as formulated in the Dutch PNH guideline. However, novel therapies are needed to further improve real‐world outcomes, such as hematological responses and quality of life.